Legal Aspects of the Value of Evidence in Notary Deed - Bisyir, Dzaky Alwan; Putra, Mohamad Fajri Mekka (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
A notary is a public official sworn in by the state to provide legal services to the public. One of the leading powers of a notary is to make a notarial deed or an authentic deed which is a form of written evidence. An authentic deed is made by or before a notary and made at the place where the deed was done and its form is strictly regulated by law. The problem raised in this research is the value of proof of a notary deed for a legal act by the parties. The research method used is a form of normative juridical law research. The type of data used is secondary data. Secondary data is obtained through a literature search/library study consisting of primary, secondary, and tertiary legal materials. The responsibility of a notary is to guarantee the truth of the existence of a legal action carried out by the parties. In practice, notaries have often considered parties to the deed, but in fact the notary deed contains something desired by the parties who bind themselves in an agreement. The notary is only authorized to write the parties’ will into a notarial deed so that the deed in question only contains a statement or original legal action of the parties’ will written using legal sentences. If the contents of the deed are disputed, then the problem should be the problem of the parties.